Science, Media, Necropolitics and Bastard Trans-feminism(s): Intro into the Thematic Whole - Gržinić, Marina (Identities: Journal for Politics, Gender and Culture, 2013)
Author(s): Marina Gržinić Title (English): Science, Media, Necropolitics and Bastard Trans-feminism(s): Intro into the Thematic Whole Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 5 Page Count: 1 Citation (English): Marina Gržinić, “Science, Media, Necropolitics and Bastard Trans-feminism(s): Intro into the Thematic Whole,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 5.